Measuring enteric methane emissions from individual dairy cows during milking by detecting eructation peaks - Hardan, Ali (2024)
Measurement of enteric methane emissions from cattle has gained interest given that cattle are a significant source of anthropogenic greenhouse gas emissions. Infrared gas analysers were used in this study to continuously measure concentration of methane every second and detect eructations when cows were being milked in robotic milking stations. Most of the cows investigated were Holstein-Friesian cows, housed at the University of Nottingham Centre for Dairy Science Innovation (CDSI) and on 17 commercial farms in the UK. The time-series signal of methane concentration was analysed using peak analysis and signal processing techniques to identify eructation peaks. The study found a high correlation (r = 0.71) between methane emissions calculated from area under eructations (integral of peaks) and amplitude of eructations using peak analysis approaches. Measurements of methane emissions obtained using an SP Guardian analyser with low gas volume and slow flow rate provided the most repeatable measurements and detected more variation among cows than other gas analysers tested. Measurements of enteric methane using signal processing were estimated to be 0.38 (s.e. 0.01) g/min, 31.8 (s.e. 0.5) g/kg dry matter intake (DMI) and 25.6 (s.e. 0.5) g/kg milk across all 18 farms studied. During early lactation methane emissions increased to 0.4 g/min at week 10 of lactation, and then was steady until week 70. This profile was similar for emissions per unit feed intake. It is concluded that signal processing can be used with different gas analysers in a breath sampling approach to reliably extract methane measurements based on amplitude of detected eructation peaks.